Effect of postpartum depression, anxiety and social support on maternal self-efficacy: comparing undocumented migrant, documented migrant and Swiss-born mothers - Sharapova, Anna; Goguikian Ratcliff, Betty (Frontiers in Psychology, 2025)
IntroductionPostpartum depression and anxiety negatively affect maternal sense of self-efficacy, which may jeopardize mother-infant bonding. Migrant women are at two to three times higher risk for postpartum depression and anxiety. Therefore, they may experience lower maternal self-efficacy, but studies on the subject are lacking. The aims of this study were (1) to compare two groups of economic migrants of differing legal status in Geneva, Switzerland, to native Swiss women in terms of postpartum depression and anxiety rates, as well as maternal sense of self-efficacy, and (2) to examine the effects of postpartum depression, anxiety, and social support on maternal self-efficacy in the three groups.MethodsA sample of 25 undocumented migrant women, 42 documented migrant women, and 41 Swiss women were interviewed at 3 months postpartum. Depression was assessed with the Edinburgh Postpartum Depression Scale and anxiety with the State–Trait Anxiety Inventory. Maternal self-efficacy was assessed with the Maternal Self-Efficacy Scale. ANOVAs and multiple regression analysis were used to test mean-level differences among the three groups and identify factors associated with low maternal self-efficacy.ResultsLegal status was associated with living conditions and influenced the rates of postpartum distress. Swiss women and documented migrant women showed low depression and anxiety rates, whereas nearly half of the sample of undocumented women reported high levels of postpartum depression and anxiety. However, despite poor postpartum mental health, undocumented women showed a higher sense of maternal self-efficacy than did documented migrants and Swiss natives. The relationship between postpartum depression, maternal self-efficacy, social support, and legal status is discussed.